Volatile organic compounds as potential biomarkers for the diagnosis of digestive diseases. A review - Vladimir I. Pilipenko (ZAO "Consilium Medicum", 2024)
Diseases of the digestive system are very common among the population around the world. Diagnosis of the diseases of this group is expensive and often invasive, which greatly limits its accessibility to the population. Increasing the time of disease development before diagnosis increases the risk of complications and adverse outcomes. The use of volatile organic compounds (VOC) as a biomarker is becoming increasingly popular due to the accuracy and ease of use. The article examines the available analytical platforms of VOCs for detecting changes in the state of the digestive system, assesses their strengths and weaknesses, provides examples of VOC assessment tool for the diagnosis of certain diseases of the digestive system - inflammatory bowel diseases, colorectal cancer, infectious diarrhea and celiac disease.